Pengaruh E-Commerce Terhadap Pola Pengeluaran Keuangan di Era Ekonomi Digital - Putri, Nabila Amelia; Amar'atus Laila; Ade Putri Indri Rohmawati; Maria Yovita R. Pandin (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research uses quantitative methods which aim to analyze the impact of trade on financial expenditure patterns in the digital economy era. Does e-commerce have an influence or not on financial spending patterns in the digital economy era? This data analysis technique involves distributing questionnaires via Google Form on social media, namely WhatsApp, which is used to collect data. The research results show that e-commerce has a better influence on financial spending patterns.